2016
DOI: 10.1097/qco.0000000000000320
|View full text |Cite
|
Sign up to set email alerts
|

New and emerging therapies for Clostridium difficile infection

Abstract: (max 200 words)Purpose of review: Clostridium difficile infection has attained high prominence given its prevalence and impacts on patients and healthcare institutions. Multiple new approaches to the prevention and treatment of CDI are undergoing clinical trials. Recent findings:Bezlotoxumab is a monoclonal antibody against toxin B that has successfully completed phase three studies, demonstrating a significant reduction in recurrent CDI when given with standard of care antibiotics. Antibiotics under developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…Vaccine development has been considered by many to be one way to control the morbidity and relapses due to CDI (Martin and Wilcox, 2016). Most studies on the development of vaccines against CDI focused on the major pathogenic determinants of C. difficile , toxin A and B (Martin and Wilcox, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccine development has been considered by many to be one way to control the morbidity and relapses due to CDI (Martin and Wilcox, 2016). Most studies on the development of vaccines against CDI focused on the major pathogenic determinants of C. difficile , toxin A and B (Martin and Wilcox, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine development has been considered by many to be one way to control the morbidity and relapses due to CDI (Martin and Wilcox, 2016). Most studies on the development of vaccines against CDI focused on the major pathogenic determinants of C. difficile , toxin A and B (Martin and Wilcox, 2016). Production of anti-toxin antibodies are considered to be the most effective defense mechanism in mediating systemic and mucosal protection against CDI in both animal models and patients (Pechine and Collignon, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that commensal bacteria cultured from the stool of healthy donors,22 sterile faecal filtrate23 and/or spores of Firmicutes derived from ethanol-treated stool from healthy donors24 may have similar efficacy to conventional FMT in treating CDI, although results of the latter approach produced disappointing outcome data when extended to a phase II clinical trial 25. For the purposes of this guideline, the BSG/HIS working group considered only studies that used the administration of manipulated whole stool (including encapsulated faeces).…”
Section: Introductionmentioning
confidence: 99%
“…Results from the phase II (ECOSPOR) trial indicate that SER‐109 did not meet the primary endpoint for reducing CDI recurrence overall. However, in high‐risk populations (in this case, those 65 years or older), SER‐109 treatment showed reduced recurrence rates (45% versus 80% recurrence risk) . Two phase III trials (ECOSPOR III–NCT03183128 and ECOSPOR IV–NCT03183141) are currently recruiting.…”
Section: Areas For Improvement and Targets For Emerging Therapiesmentioning
confidence: 99%